Lipschitz (q, p, E)-summing operators on injective Lipschitz tensor products of spaces - Tallab Abdelhamid (Moroccan Journal of Pure and Applied Analysis, 2020)
In this paper, we introduce the notion of (q, p)-mixing operators from the injective tensor product space E ̂⊗∈F into a Banach space G which we call (q, p, F)-mixing. In particular, we extend the notion of (q, p, E)-summing operators which is a special case of (q, p, F)-mixing operators to Lipschitz case by studying their properties and showing some results for this notion.